113=276-q

Simple and best practice solution for 113=276-q equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 113=276-q equation:


Simplifying
113 = 276 + -1q

Solving
113 = 276 + -1q

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add 'q' to each side of the equation.
113 + q = 276 + -1q + q

Combine like terms: -1q + q = 0
113 + q = 276 + 0
113 + q = 276

Add '-113' to each side of the equation.
113 + -113 + q = 276 + -113

Combine like terms: 113 + -113 = 0
0 + q = 276 + -113
q = 276 + -113

Combine like terms: 276 + -113 = 163
q = 163

Simplifying
q = 163

See similar equations:

| 5e^8t=6e^7t | | 8-3(x+1)=20 | | 15x+x-12=63 | | 2+x+19=2x+33 | | 2x+5(x-4)=8 | | 10b+10+2b=-10+8b | | -6x-x=20 | | 19x-(8x-4)=92 | | (X+78)x+41=95 | | -2=b-11 | | 126=-7(-5a-3) | | 3(x+2)=2(2+x) | | 2(-6-5x)=68 | | 5x+6-x=7+5x-6 | | (X+78)x+42=95 | | 3x+7y=62 | | 3(x+40)= | | (5x-4)(5x+4)=80 | | b-4+2b=27 | | 5-3x=10x-35+2 | | -7(c+372)+620=-185 | | 4(5z+1)-6=178 | | 2(n+7)=5n+8 | | b-4+26=27 | | (X+41)x+78=95 | | 53=29-4(x-4) | | (X+41)+x+78=95 | | 7+2[m-4]=3 | | 90=(3x+13)(5x-7) | | 20%*5000= | | (3x^2+7x-4)+(2x^2-3x-9)= | | 5-9n=31 |

Equations solver categories